The Administrative Court Judges Paradigm on Justice and the Protection of the Awyu Indigenous People's Rights in Environmental Permit Dispute - Masna Nuros Safitri; Syarifudin; Inarotul Insyaniyah; Gita Ranjani; Gladys Donna Karina; Jelita Septiani Aprisal (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
The environmental permit dispute between the Awyu Indigenous People and PT Indo Asiana Lestari highlights challenges in protecting indigenous rights and environmental justice in the Administrative Court. The main issue lies in the legal paradigm that prioritizes procedural aspects and material losses, while neglecting local wisdom, community participation, and long-term ecological impacts. This study aims to analyze the judicial paradigm in Administrative Court rulings and its implications for the protection of indigenous rights and environmental sustainability. Using normative legal research and the critical legal studies approach, the findings indicate that administrative court decisions reinforce structural injustice by limiting the definition of harm to material losses, without considering social and ecological damages. As long as the law remains unchanged, judges will continue to adhere to a procedural and formalistic approach. Therefore, legal reform is necessary, particularly a review of Article 53(1) of the Law on Administrative Court, to enable judges to consider social and ecological impacts in their decisions.